الكلمات الواردة في الكتب المقررة لمادة اللغة العربية بالمدارس الثانوية بماليزيا: دراسة لغوية حاسوبية - Khadijah Khalilah Abdul Rashid (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This study provides a word list of the Arabic textbooks used in Malaysian government secondary schools in 2012 from Form One to Form Five. The word list was produced from a corpus of the Arabic textbooks. The research employed descriptive and analytical research methods. The corpus will be useful to students and teachers for learning and teaching purposes, as well as to those who write textbooks and exercise books for the Arabic Language syllabi. This study concludes that the word )في( was the most commonly repeated word as it occurred 605 times in Form One corpus, 523 times in Form Two corpus, 639 times in Form Three corpus, 1,030 times in Form Four corpus and 790 times in Form Five corpus. As for nouns, the word )الآتية( was the most frequently repeated as it occurred 638 times and the verb )اقرأ( was the most commonly repeated as it occurred 244 times, while the preposition )في( was the most regularly repeated as it occurred 3,587 times.